The Anthropocene! Beyond the natural? - CCC - Rolston, Holmes, 1932-2025, speaker (Colorado State University. Libraries, 2012)
We are now entering the Anthropocene Epoch - so runs a recent enthusiastic claim. Humans can and ought go beyond the natural and powerfully engineer a better planet, managing for climate change, building new ecosystems for a more prosperous future. Perhaps the Anthropocene is inevitable. But: Rejoice? Accommodate? Accept it, alas? Perhaps the wiser, more ethical course is not so much "beyond" as "keeping the natural in "symbiosis" with humans. Enter the Semi-Anthropocene! Basically Natural! Carefully!
Presented at the Fall 2012 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Power and Ethics in (Collaborative) Conservation", August 28, 2012, Colorado State University, Fort Collins, Colorado. This series focused on the work that the CCC's Collaborative Conservation Fellows have been doing across the Western U.S. and around the world.
Holmes Rolston, III, is University Distinguished Professor and Professor of Philosophy. Emeritus, at Colorado State University and a founder of environmental ethics as a philosophical discipline. His books include: Philosophy Gone Wild, Environmental Ethics, Conserving Natural Value, Science and Religion: A Critical Survey, Three Big Bangs: Matter-Energy, Life, Mind. His most recent is A New Environmental Ethics: The Next Millennium for Life on Earth. He gave the Gifford Lectures, University of Edinburgh, 1997-1998, published as Genes, Genesis and God. Advocating environmental ethics, he has lectured on seven continents. He is featured in Joy A. Palmer, ed., Fifty Key Thinkers on the Environment. He won the Templeton Prize in 2003, an award worth well over a million dollars, and more than a Nobel prize, awarded by Prince Philip in Buckingham Palace.
Includes recorded speech and PowerPoint presentation.
Accessibility features: Unedited transcript.
Keywords: global environmental change; effect of environment on human beings; effect of human beings on nature